HOW TO FORGE A FROGMAN : A RECRUIT'S ACCOUNT OF BASIC TRAINING IN SINGAPORE'S NAVAL DIVING UNIT - West, Max (Marshall Cavendish Editions, 2017)
Half-American and half-Singaporean, Max West grew up in Singapore without having ever heard of the Naval Diving Unit. Upon graduating from high school, however, he was conscripted for two years of mandatory military service. He found himself thrust into NDU, Singapore's elite naval special forces formation, as one of just two Eurasians in his enlistment class. In this candid firsthand account, West recounts the grueling training he endured and the deep camaraderie he and his teammates forged throughout their journey. West offers an accurate, unrestrained depiction of life as a trainee, revealing what it takes to succeed as a combat diver in the Singapore Armed Forces. National Service is a shared crucible borne by every Singaporean son. Unrestrained in its frankness and compellingly told, How to Forge a Frogman is a true, coming-of-age tale set in a uniquely Singaporean setting